Negative parity baryon decays in the 1=Nc expansion - Jayalath, C. (2011)
The partial decay widths of lowest lying negative parity baryons belonging to the 70-plet of SU(6) are analyzed in the framework of the 1/Nc expansion. The channels considered are those with single pseudoscalar meson emission. The analysis is carried out to sub-leading order in 1/Nc and to first order in SU(3) symmetry breaking. Conclusions about the magnitude of SU(3) breaking effects along with predictions for some unknown or poorly determined partial decay widths of known resonances are obtained.